EMPOWERING PARENTS THROUGH HEALTH EDUCATION: ENHANCING COMPETENCY IN PREMATURE INFANT CARE - Puspita, Enny; Sholikhah, Dwi Uswatun (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2025)
Background: Premature birth remains a leading cause of neonatal morbidity and mortality globally. Parents of premature infants often face challenges in providing proper care after hospital discharge due to limited knowledge, inadequate caregiving skills, and a lack of readiness. Health education plays a vital role in improving parental competency and ensuring safe and effective home care. Objectives: This study aimed to evaluate the effect of health education on improving the knowledge, caregiving skills, and readiness of mothers in caring for premature infants. Methods: A quasi-experimental pre-posttest design was conducted involving 25 mothers whose premature infants were admitted to the neonatal unit of RSI Siti Hajar Sidoarjo. The intervention included structured health education using printed leaflets and direct nursing demonstrations. Data were collected through validated questionnaires and observation checklists before and after the intervention. Statistical analysis was conducted using the Chi-square test with a significance level of p < 0.05. Results: Before the intervention, 76% of mothers demonstrated poor knowledge, 100% lacked caregiving skills, and 100% were unprepared for home care. Post-intervention, 76% exhibited good knowledge, 80% showed adequate caregiving skills, and 84% were ready to care for their infants. All improvements were statistically significant (p = 0.000). Conclusion: Health education significantly improved maternal knowledge, caregiving skills, and readiness in caring for premature infants. It is recommended that structured educational programs be routinely integrated into neonatal discharge planning to support safe and effective home care.